2023
DOI: 10.3390/ani13233686
|View full text |Cite
|
Sign up to set email alerts
|

First Molecular-Based Confirmation of Dermacentor marginatus and Associated Rickettsia raoultii and Anaplasma marginale in the Hindu Kush Mountain Range

Iftikhar Ahmad,
Shafi Ullah,
Abdulaziz Alouffi
et al.

Abstract: Ticks of the genus Dermacentor Koch, 1844 (Acari: Ixodidae) are poorly known systematically due to their habitation in harsh topographic environments and high mountains. Dermacentor ticks are diversely distributed in the Palearctic, Nearctic, and Oriental regions. There is no available information on the occurrence of Dermacentor marginatus in Pakistan; thus, the current investigation aimed the first morphological and molecular confirmation of this species and associated Anaplasma marginale and Rickettsia raou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, they are among the most neglected tick genera in the Oriental region, including Pakistan. Importantly, research in Pakistan has considerably focused on the exploration of ticks and tick-borne pathogens in the last half-decade ( 4 , 5 , 9 , 39 , 53 65 ). This study provides the first morphological and molecular record of A. coniceps and Dermacentor sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they are among the most neglected tick genera in the Oriental region, including Pakistan. Importantly, research in Pakistan has considerably focused on the exploration of ticks and tick-borne pathogens in the last half-decade ( 4 , 5 , 9 , 39 , 53 65 ). This study provides the first morphological and molecular record of A. coniceps and Dermacentor sp.…”
Section: Discussionmentioning
confidence: 99%
“…Although demonstrating characteristics of both the Palearctic and Oriental regions, the knowledge regarding the genera Alectorobius and Dermacentor is limited within Pakistan. No tick species from the Alectorobius genus has been reported, while only Dermacentor raskemensis and Dermacentor marginatus have been identified morphologically or molecularly within the Dermacentor genus in this country ( 39 – 43 ). To address this knowledge gap, in this study, we reported the occurrence and genetic characterization of Dermacentor and Alectorobius species in Pakistan using morphological and molecular approaches.…”
Section: Introductionmentioning
confidence: 99%